PERFORMANCE ANALYSIS OF HELIUM INVENTORY CONTROL OF RGTT200K COOLING SYSTEM - Sriyono Sriyono; Rahayu Kusumastuti; Sofia Butarbutar; Geni Rina Sunaryo (SIGMA EPSILON - Buletin Ilmiah Teknologi Keselamatan Reaktor Nuklir, 2015)
RGTT200K is a power reactor, designed based on HTGR tech-nology having capability to operate at high temperatures. RGTT200K features are 200 MWth power, helium-cooled, graphite moderator and reflector, pebble fuel type, and uses the Brayton direct cycle. Helium Inventory Control System (HICS) is one of its safety system which maintains the pressure, the helium coolant quality and quantity to meet safety requirements. The HICS consists of 3 subsys-tems, namely: Inventory Control System (ICS), Helium Purification System (HPS), and Helium Make-Up System (HMS). All of the systems have the function to maintain pressure, helium quality and quantity so that the reactor can operate reliable and safely. This paper discusses the performance of the ICS, which is integrated to the reactor coolant. The research objective was to determine the helium storage tank response rate, when primary coolant is overpressured and depressurized. The methodology used in this research is modeling and simulation by using ChemCAD. In previous re-search, the HPS, ICS and HMS have been modeled but have not been integrated yet in to the primary coolant. The simulation results showed that the time required for the injection tank back to the cool-ant normal pressure of 52 bars, due to depressurization up to 5 % was 160 seconds. While the time required for bleeding / blowdown to the storage tanks due to overpressurization up to 5 % was 186 seconds.